Mekanisme Pertahanan Ego Pada Tokoh Cakrawala Dalam Novel Not Me Karya Caaay (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
The purpose of this study is to describe the ego defense mechanism in the character Cakrawala in the novel Not Me by Caaay using the study of Sigmund Freud. This research method uses qualitative research methods. The data collection technique used in this study is a literature study. The method used uses the approach of Literary Psychology. The findings obtained show that the Cakrawala character has an ego defense mechanism in the form of repression, denial, reaction formation, rationalization and fantasy and streotype.